Techno-stress in the workplace: triggers, outcomes, and coping strategies with a special focus on generational differences. (17th December 2021) - Spiess, Teresa; Ploder, Christian; Bernsteiner, Reinhard; Dilger, Thomas
Being part of the modern world of work usually means having to deal with information and communication technologies. These technologies are designed to enhance task performance and productivity. However, sometimes they can have the opposite effect, e.g., triggered by mechanisms like techno-stress. This paper analyses whether this form of ICT-related stress can be connected to different triggers, outcomes, and coping strategies for Generation Y and Babyboomer generation knowledge workers. Ten episodic interviews led to the conclusion that all interview partners face various forms of techno-stress during their work. For the Generation Y, techno-stress is largely created by the techno-stress creators' techno-overload and techno-invasion. For the Babyboomer generation, techno-stress is triggered by other techno-stress creators, namely by techno-complexity and techno-uncertainty. Furthermore, there is also a difference in how the two generations deal with techno-stress. Members of Generation Y focus on problem-oriented and emotional coping strategies, whereas members of the Babyboomer generation mostly use emotional coping strategies. Moreover, the outcomes of techno-stress vary. While Generation Y experiences role conflicts due to techno-invasion and productivity losses due to techno-overload, for the Babyboomer generation techno-stress reduces productivity owing to techno-uncertainty.